Integrasi Matematika dan Nilai-nilai Keislaman Pada Konsep Aljabar Linier - Karladinata, Rahayu; Nuraida, Ida (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 5 No 1 (2025): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami), 2025)
This research aims to describe the integration of mathematics and Islamic values in the concept of Linear Algebra from the perspective of the Qur'an and Hadith. The method used is literature review with the basic references being the Al-Qur'an, hadith. The data obtained was then analyzed using a descriptive or narrative qualitative approach. Data collection was carried out using the documentation method by searching for data from literature related to the research topic. Considering the broad scope of Linear Algebra concepts, this research is limited to the concepts of matrices, systems of linear equations, and bases. After identification, several verses were found in the Al-Qur'an which contained the concept of matrix, solving problems of the linear equations systems and hadiths which contained problems solving of basis. Based on the analysis and discussion, it is concluded that: (1) the definition of a matrix is integrated into the Islamic values contained in Q.S.Ash-Shaff :4 which is a representation of rows and columns in a matrix with rows on the rows pray, (2) the matrix multiplication operation is integrated into the Islamic values contained in Q.S. Al-an'am:160 which is a representation of charity from human actions, (3) the nature of matrix identity is integrated into Islamic values as stated in Q.S. Ali-Imran:64 and Q.S. Fussilat:33 which is a representation of the identity of a Muslim, (4) problem solving of equations linear systems is integrated into the Islamic values contained in Q.S. Al-Baqarah:286, Q.S. Al-Insyirah:5-6; Q.S. Ar-Rad:11 which represents the way out of all problems according to Islam, and (5) basis, in its solution it combines the concepts of linear independent and spanning vectors with certain conditions, this is if it is integrated into the Islamic values contained in the Q.S. An-Nisa:101 and several Hadiths that represent the use of congregational qasar prayers for travelers at a certain distance, this shows that Islam is a religion that makes things easier. If a case cannot be carried out properly because of some reason, there are conveniences (rukhsah) to replace or lighten the work.